Penerapan Customer Relationship Management dalam Meningkatkan Kepuasan dan Loyalitas Pelanggan PPMU Foundation Bandung - Syaifuddin (SINTESA, 2022)
PPMU Foundation is a non-profit organization engaged in social education with a focus on the issue of equity in access to education for the society, especially the poor. The organization has a mission to support the community in accessing education through funding programs from donors. To build a good relationship with donors, an effective information system is needed. Interactive Customer Relationship Management (i-CRM) information system is one of the best alternative solutions. I-CRM can provide an interaction between PPMU Foundation and donors interactively. Collecting data is conducted by observation, interviews, questionnaires and literature studies. Information system development using RAD model, which includes UML, use case diagram, sequence class, statechart and activity. The purpose of the research is to build interactive customer relationship management (i-CRM) in increasing donor satisfaction and loyalty. The result of this research is that the i-CRM website can provide interactive communication with donors, with 76.13% of donors stated that the information provided by i-CRM is good, 55% stated that i-CRM is easy to use, and 90% stated that i-CRM improves service quality.